FUZZY EVALUATION OF VISUAL CONNECTEDNESS IN THERMOGRAPHY IMAGES OF CYLINDRICAL SURFACE - Jaworski, Tomasz; Kucharski, Jacek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
This article presents an idea of visual connectedness measure between components in thermography images of rotating steel roller, cylindrically shaped. Both definition and method of measure calculus is given along with a short discussion.